Optimization of Chromium (VI) Adsorption using Microalgae Biomass (Spirulina sp.) and its Application in Leather Tannery Waste - Adetya, Nais Pinta; Arifin, Uma Fadzilia; Anggriyani, Emiliana; Rachmawati, Laili (CHEESA: Chemical Engineering Research Articles, 2023)
This study was conducted to examine the adsorption of Cr (VI) metal using Spirulina sp (inactive) biomass and its application in leather tannery wastewater. The treatment was carried out to determine the influence of independent variables on Cr (VI) adsorption with variations in pH, contact time, and metal solution concentration. The values of the solution pH, adsorption time, and concentration of the best metal solution were used to determine the center points of the optimization variables through Response Surface Methodology (RSM). The results showed that based on the FTIR test, macromolecules present in Spirulina sp biomass included amino, carboxylate, and hydroxy groups. The combination of factor variables that produced the optimum response was at pH 3.165, contact time of 66.58 minutes, and Cr (VI) metal ion solution concentration of 22.9 mg/L, resulting in a Cr (VI) adsorption efficiency of 69.66%. The adsorption pattern was included in the Freundlich adsorption isotherm, and the application of Spirulina sp biomass adsorbent to tannery waste reduced the concentration of Cr (VI) from 3.9 g/L to an undetectable level at <1.4 g/L.